1999
DOI: 10.1063/1.370543
|View full text |Cite
|
Sign up to set email alerts
|

High-field electrical conduction in polyimide films

Abstract: Capacitance transient spectroscopy in metal-insulator-metal systems and its application to the determination of trap parameters in polyimide filmsElectrical conduction current in polyimide films has been measured at high fields ͑Ͼ1.4 MV cm Ϫ1 ͒ using a Au metal ͑M͒-polyimide film ͑P͒-p-silicon ͑S͒-MIS structure. On the basis of the currentvoltage characteristics coupled with the capacitance-voltage characteristics measured under various conditions, it is found that electrical conduction at high fields is mainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(32 citation statements)
references
References 32 publications
2
29
0
1
Order By: Relevance
“…Because of the large energy bandgap, the potential barrier height for electrons injected from the electrical contacts to the polymer is usually smaller than that for hole injection, implying that electron injection is dominant in insulating polymers under normal practical conditions. [17][18][19] The nature of the bulk trapping states in polymers has been studied by several investigators. 20,21 Their experimental results have indicated that most bulk traps are acceptor-like electron traps and donor-like hole traps.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the large energy bandgap, the potential barrier height for electrons injected from the electrical contacts to the polymer is usually smaller than that for hole injection, implying that electron injection is dominant in insulating polymers under normal practical conditions. [17][18][19] The nature of the bulk trapping states in polymers has been studied by several investigators. 20,21 Their experimental results have indicated that most bulk traps are acceptor-like electron traps and donor-like hole traps.…”
Section: Resultsmentioning
confidence: 99%
“…4,[22][23][24] It is most likely that the electrons are injected into the polymer from the metallic cathode mainly by FowlerNordheim tunneling. [17][18][19] These injected electrons will quickly become trapped after one or a few scatterings. According to Kao's model, 5 a transition of an injected electron from an upper energy state (e.g., conduction bands) to a lower one (e.g., traps) due to trapping or recombination involves an energy release.…”
Section: Resultsmentioning
confidence: 99%
“…The data in Figs. [4][5][6][7] show that in the temperature range from 370 to 470 K the β 2 relaxation is entering. For the β relaxation various mechanisms have been proposed involving motions that, while still essentially local in character, encompass larger portions of the repeat unit that respond in a correlated manner.…”
Section: Discussionmentioning
confidence: 97%
“…Consequently, it has a high potential for microelectronic applications, e.g., as interlayer dielectrics, flexible circuitry substrates, stress buffers, and passivation layers. PI is a hydrophilic polymer and its dielectric properties largely depend upon absorbed water or humidity [4][5][6]. A good deal of work on electrical conduction in PI at low fields [7][8][9][10][11] and high fields [6,12] has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…1 Due to their excellent thermal, electrical, and mechanical properties, they appear as very interesting for high temperature and high electric field applications. [2][3][4] Although the electrical properties of PI films have been largely investigated since many years, 5-9 their operating limit under high electric field at high temperature still remains unknown up to now. As PI is known to fail via a thermal process, 10,11 resulting from the formation of a spacecharge-limited-current mechanism, 12,13 they have to be used below the temperature runaway when high electric fields are applied to their bulk.…”
mentioning
confidence: 99%